Transhumanism: The Epitome of Doom and Gloom - Noorulain Hyder; Muhammad Liaquat Raza; Azfar Athar Ishaqui (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2017)
Ever since the idea of "Transhumanism" came into being, it has divided our society into two opposing factions i.e. the bioconservatives and transhumanists. The  transhumanist  movement  is  based  on  the idea that enhancements should be made in  humans  through  technology  while  bioconservatives  oppose this idea. Transhumanism is already feared to  be  world's  most  dangerous  idea  by  bioconservatives such as Francis Fukuyama, as it is not justified or proven yet that transhumanism is safe for our future. The notion is believed to be not only de-humanising but also poses many threats to the rest of humanity.  As  explicitly  suggested  by  bioconservatives  human  enhancing  technologies  are more of a bane than a boon. Furthermore, many of the transhumanist technologies  have  many demerits to them. Bioconservatives believe that the technological enhancements will lead to obscenity and be a blemish on the human race. It is highly possible that humans will suffer from autocracy by the hands of the posthumans, since the posthuman age will certainly give rise  to  several  moral  di- lemmas, such as racism, which will plague the human world. There are four fundamental aspects of transhumanism; nanotechnology, biotechnology, information technology (IT)  and  cognitive  sciences,  which come with many promising advantages, but can also turn our future into a dystopia. Even with constant opposition from the bioconservatives, the dark scenarios related with the ascend of the  transhuman era are inevitable and the amalgamation of machines with man is equivalent to forfeiting true humanity.